ANALISIS AKUNTABILITAS DALAM PENGELOLAAN DANA KELURAHAN DI KECAMATAN AERTEMBAGAKOTA BITUNG - Christine Monica Saren; Jantje J. Tinangon; Jessy D. L. Warongan (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2022)
This study aims to analyze accountability in the management of village funds in Aertembaga District Bitung City. The study used a qualitative descriptive method. Data were obtained through interview techniques and documentation studies. Data collection techniques through interviews, observation, and documentation. Triangulation method is used in testing data sources and credibility. The transcript data described from the interviews were analyzed using analytical methods then given a theme/coding and conceptualized scientific statements. The results of the interpretation are concluded in the narrative text. The results showed that the management of village funds in Aertembaga District in this case activities, budgeting, coaching and supervision had been carried out in accordance with Permendagri No. 130 of 2018. Meanwhile, there are still 2 problematic stages, namely the implementation of activities and administration and accountability that are not in accordance with Permendagri No. 130 of 2018. This is due to the absence of transparency regarding the results of the implementation of the budget work plan and the absence of information disclosure regarding the accountability report for the management of village funds to the public. The obstacles found were the bureaucratic structure, human resources, communication and attitude of the implementers. To overcome these obstacles, the kelurahan government needs to provide additional guidance and training for kelurahan officials so that the management of kelurahan funds can be managed effectively and efficiently. The results of the analysis carried out in terms of honesty accountability and legal accountability are categorized as satisfactory, in terms of program accountability it is satisfactory, in terms of managerial accountability it is very good, and in terms of policy accountability it is good.